IMPROVE THE BEE FOOD BASE BY PLANTING SAP AND POLLINATING TREES AND SHRUBS - Tolipova Kholidaxon Sherali kizi; Uktamova Zebokhon Nosirjon kizi; Okhunova Durdona Erkinjon kizi; Azizov Rahmatillo Olimjon ugli (American Journals, 2023)
This article provides information on increasing the yield of fruits and obtaining high-quality honey by planting trees and shrubs that provide nectar and pollen, improving the food base of bees.
Keywords: Bees, bee feeding, bee milk, bee wax, bee venom, pollen, flower.